Membangun Jiwa Entrepreneur Pada Generasi - Z Di SMK Negeri 4 Palangka Raya - rahman, rahman_rahman; Fendy Hariatama; Hidayati; Sundari (Jurnal Pengabdian Kampus, 2024)
Community Service activities were carried out on Wednesday, November 08, 2023 in the XI DKV 1 classroom of SMKN 4 Palangka Raya. Participants who participated in this activity were 25 students of class XI SMKN 4 Palangka Raya, The community service activities carried out aim to build an entrepreneurial spirit in generation Z, namely class XI students of SMKN 4 Palangka Raya. This community service activity was carried out in the school environment of SMKN 4 Palangka Raya. The results of this community service activity show that the students of class XI DKV 1 who participated in this socialization activity were very enthusiastic. This is reflected in the participation of students in activities from the beginning of implementation to the end of implementation, so active in discussion sessions during the activity, seen from the many training participants who asked questions related to becoming an entrepreneur.